Chronic tobacco smoking and neurocognitive impairments in adolescents and young adults: a systematic review and meta-analysis - Elatfy, Ahmed; Vrahimis, Sebastian; Conti, Aldo; Baldacchino, Alexander (Frontiers in Psychiatry, 2024)
There is a lack of robust research investigating the association between neurocognitive impairments and chronic tobacco smoking in adolescents/young adults. Therefore, a systematic review and meta-analysis were conducted to examine this association by pooling cross-sectional studies published from 1980 to 2023. The systematic review assessed the neurocognitive performances between chronic tobacco smokers and non-smokers in each study. The meta-analysis included six studies that compared chronic tobacco smokers against non-smokers using neuropsychological tests covering three neurocognitive domains. The results showed a cross-sectional association between impairments in motor impulsivity across two aspects: reaction delay and incongruent errors, with the effect size being (SDM = 0.615, p = 0.000) and (SDM = 0.593, p = 0.000) respectively. However, no significant associations were found for intelligence (SDM = 0.221, p = 0.425) or working memory (SDM = 0.150, p = 0.581). This study highlights the need for further research to explore a greater number of neurocognitive domains in the context of chronic smoking in adolescents/young adults, particularly motor impulsivity, intelligence and working memory, as well as the socioeconomic factors involved. There is also a need to further study the effects of emerging alternative nicotine administration methods in this age group.